Paleobiolinguistics of New World Crops and the Otomanguean Language Family - Cecil H. Brown (Ethnobiology Letters, 2015)
Several studies recently published in Ethnobiology Letters treat respectively the paleobiolinguistics of chili pepper, manioc, maize, and the common bean in New World language families. This includes the Otomanguean family of Mexico, one of the oldest language groups of the hemisphere, whose parent language may have been spoken at the latest around 6500 years ago. This communication addresses the possibility that Otomanguean paleobiolinguistics should be considered tentative since languages of the grouping are not yet conclusively demonstrated to be descended from a common ancestor. This challenges the proposal that words for chili pepper, manioc, and maize were in vocabularies of languages spoken two thousand or more years before development of a village-farming way of life in the New World.